Is academic freedom under siege? University and free speech - Sztajer, Sławomir (Humaniora. Czasopismo Internetowe, 2022)
Freedom of speech is an essential dimension of academic freedom. Without free speech, a university’s mission, which includes innovative research and high-quality teaching, cannot succeed. However, in recent years, the foundation of free speech on campus has been compromised. There are not only an increasing number of ideas and practices that challenge the liberal conception of free speech (e.g., political correctness, safe space, trigger warnings, verbal purification, and disinviting) but also theoretical justifications for such ideas and practices. This article focuses on the current discussion in the United States, where the debate on academic freedom is the most heated. The situation in the United States is important because it influences academic life in other developed countries. It can be argued that free speech does not exclude building a safe and inclusive campus environment. However, because of its central role in the university’s mission, freedom of speech cannot be traded against other values regardless of their importance.